How Big is My Neighborhood? Individual and Contextual Effects on Perceptions of Neighborhood Scale. Issue 1 (11th August 2012) - Coulton, Claudia J.; Jennings, M. Zane; Chan, Tsui
Abstract: Neighborhood is a social and geographic concept that plays an increasingly important role in research and practice that address disparities in health and well‐being of populations. However, most studies of neighborhoods, as well as community initiatives geared toward neighborhood improvement, make simplifying assumptions about boundaries, often relying on census geography to operationalize the neighborhood units. This study used geographic information system (GIS) tools to gather and analyze neighborhood maps drawn by residents of low‐income communities in 10 cities. The median resident map size was approximately 30 percent smaller than the median census tract, but 25 percent of residents viewed their neighborhood as quite small (less than one‐fifth of the typical census tract). Multi‐level modeling showed significant within context variation in perceived neighborhood scale. Longer term residents with higher education and income and who were more engaged in the neighborhood held more expansive views. But there were also contextual influences with higher density and mixed use areas associated with smaller perceived neighborhoods, and higher collective efficacy associated with larger neighborhood sizes. Artificially imposed neighborhood units may misrepresent resident experience, but GIS tools can be used to craft more authentic neighborhood definitions for research and practice.